Oligodendroglial α‐synucleinopathy‐driven neuroinflammation in multiple system atrophy. (31st January 2019) - Hoffmann, Alana; Ettle, Benjamin; Battis, Kristina; Reiprich, Simone; Schlachetzki, Johannes C. M.; Masliah, Eliezer; Wegner, Michael; Kuhlmann, Tanja; Riemenschneider, Markus J.; Winkler, Jürgen
Abstract: Neuroinflammation and oligodendroglial cytoplasmic α‐synuclein (α‐syn) inclusions (GCIs) are important neuropathological characteristics of multiple system atrophy (MSA). GCIs are known to interfere with oligodendroglial maturation and consequently result in myelin loss. The neuroinflammatory phenotype in the context of MSA, however, remains poorly understood. Here, we demonstrate MSA‐associated neuroinflammation being restricted to myeloid cells and tightly linked to oligodendroglial α‐syncleinopathy. In human putaminal post‐mortem tissue of MSA patients, neuroinflammation was observed in white matter regions only. This locally restricted neuroinflammation coincided with elevated numbers of α‐syn inclusions, while gray matter with less α‐synucleinopathy remained unaffected. In order to analyze the temporal pattern of neuroinflammation, a transgenic mouse model overexpressing human α‐syn under the control of an oligodendrocyte‐specific myelin basic protein (MBP) promoter (MBP29‐hα‐syn mice) was assessed in a pre‐symptomatic and symptomatic disease stage. Strikingly, we detected an increased neuroinflammation in regions with a high α‐syn load, the corpus callosum and the striatum, of MBP29‐hα‐syn mice, already at a pre‐symptomatic stage. Furthermore, this inflammatory response was restricted to myeloid cells being highly proliferative and showing an activated, phagocytic phenotype. In contrast, severe astrogliosis was observed only in gray matter regions of MSA patients as well as MBP29‐hα‐syn mice. To further characterize the influence of oligodendrocytes on initiation of the myeloid immune response, we performed RNA sequencing analysis of α‐syn overexpressing primary oligodendrocytes. A distinct gene expression profile including upregulation of cytokines important for myeloid cell attraction and proliferation was detected in α‐syn overexpressing oligodendrocytes. Additionally, microdissected tissue of MBP29‐hα‐syn mice exhibited a similar cellular gene expression profile in white matter regions even pre‐symptomatically. Collectively, these results imply an early crosstalk between neuroinflammation and oligodendrocytes containing α‐syn inclusions leading to an immune response locally restricted to white matter regions in MSA.